2011
DOI: 10.2224/sbp.2011.39.8.1105
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five Personality Traits And Risky Sport Participation

Abstract: The purpose in this study was to examine differences between risky sport participants and nonparticipants using the Big Five (McCrae & Costa, 1997) personality traits. The sample included 328 individuals ranging in age from 18 to 53 (M = 23.42 and SD = 3.98). The Five Factor Personality Inventory developed by Somer, Korkmaz, and Tatar (2002) was used to measure personality traits. The results showed that risky sport participants have significantly higher levels of extraversion and openness to experience a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 0 publications
9
64
0
4
Order By: Relevance
“…Although some studies have shown similar results, Kajtna (2013) says that recreational athletes are more open then high-risk sports athletes. We can confirm findings of Tok (2011) that recreational athletes have higher results in conscientiousness. On the other hand, some studies indicated different findings (Kajtna, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although some studies have shown similar results, Kajtna (2013) says that recreational athletes are more open then high-risk sports athletes. We can confirm findings of Tok (2011) that recreational athletes have higher results in conscientiousness. On the other hand, some studies indicated different findings (Kajtna, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Based on The Big Five model, Big Five Questionnaire (BFQ) and Big Five Observer (BFO) were made in Italy (Caprara, Barbaranelli, Borgogni, Bucik, & Boben, 1997). Tok (2011) has made interesting research on highrisk sports athletes and people who do not participate in such activities, using BFQ. There were many significant findings: high-risk sports athletes were more open in openness for experience, extraversion was found as an important factor, correlated with high-risk sports, people who are more neurotic are easily stimulated with stimuli whose rewards are pleasant sensations and experiences, high-risk sports athletes had lower result in neuroticism and conscientiousness.…”
Section: Introductionmentioning
confidence: 99%
“…The Study of Tok (2011) revealed that people who participate in dangerous sports are characterized with higher levels of extraversion and openness to experience and characterized with lower levels of conscientiousness and neuroticism in their traits. The study revealed also that estimation of Big Five personality traits can be valuable to check individuals' inclination to enter adventures or share risky sports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, risk-focused, adventure-related nature sports have been performed with increasing popularity and risk perception in extreme sports has been researched in recent times (Pedersen, 1997;Vagias et al, 2005). A study concerning risky sports indicated that personal characteristics such as extraversion and openness were at high levels in individuals engaged in surfing, climbing and diving as risky sports, conscientiousness and neuroticism (a personal characteristic defined as tension and emotional imbalance were at low levels (Tok, 2011). Risk-taking behaviors in extreme sports such as skydiving, surfing and mountaineering are often perceived as different issues in various fields (e.g., gambling, reckless driving or sexual behavior) because of their greater social acceptability (Castanier, Le Scanff, & Woodman, 2010).…”
Section: Introductionmentioning
confidence: 99%